1988
DOI: 10.3109/00365528809090758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Long-Acting Somatostatin Analogue SMS 201–995 on Small-Intestinal Interdigestive Motility in the Dog

Abstract: The long-acting somatostatin analogue SMS 201-995, also called Sandostatin, is used in the treatment of acromegaly and peptide-secreting tumors. Little is known about its effect on gut motility, although such an effect might be expected considering the spectrum of activities of its parent molecule, somatostatin. We have studied the effect on the interdigestive motility of intravenous boluses of 0, 0.1, 0.5, 1.5, and 5.0 micrograms/kg of this analogue in 10 dogs with bipolar electrodes implanted along the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Normal subjects showed propagative intestinal patterns during fasting with mean (SD) [1][2][3][4][5] (1 0) phase III complexes occurring every three hours (Fig 1). In contrast, none of the patients with scleroderma with pseudo-obstruction and bacterial overgrowth had any spontaneous duodenal phase III activity (Fig 1).…”
Section: Short Term Effects Of Octreotide On Intestinal Motilitymentioning
confidence: 99%
“…Normal subjects showed propagative intestinal patterns during fasting with mean (SD) [1][2][3][4][5] (1 0) phase III complexes occurring every three hours (Fig 1). In contrast, none of the patients with scleroderma with pseudo-obstruction and bacterial overgrowth had any spontaneous duodenal phase III activity (Fig 1).…”
Section: Short Term Effects Of Octreotide On Intestinal Motilitymentioning
confidence: 99%
“…It might be possible that octreotide directly reduced the production of intestinal gas. However, somatostatin stimulates intestinal motility in normal individuals (16) and octreotide is known to produce a similar effect in dogs (17). Indeed, Soudah et al ( 1 8) confirmed that octreotide increases intestinal motility in patients with progressive systemic sclerosis.…”
Section: Discussionmentioning
confidence: 55%
“…The type of octreotide-induced phase-3-like contractions was analyzed according to the criteria described by Peeters et al, 16 who defined phase-3-like contractions seen either in jejunal or ileal sites as "isolated" contractions, those propagating from jejunum to ileum as "propagated" contractions, and those observed simultaneously in both the jejunum and the ileum as "simultaneous" contractions. The maximum diameter of the bowel graft was measured in radiographs before and 30 minutes after octreotide injection.…”
Section: Discussionmentioning
confidence: 99%
“…16 Since the extrinsic nerve has been shown to modulate initiation or propagation, or both, of phase 3 contractions in the small bowel, 25 denervation may have influenced the pattern of phase-3-like contractions in the intestinal grafts.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation